2013
DOI: 10.1002/jbt.21540
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Bioactive Flavonol, Icariin, with the Essential Human Solute Carrier Transporters

Abstract: Solute carrier transporters (SLCs), in particular the organic anion transporting polypeptides (OATPs) and organic anion/cation transporters (OATs/OCTs), are responsible for the cellular entry of many clinically important drugs in body. They largely influence drug safety and efficacy. Icariin is a flavonol widely present in many herbal preparations, which is used to improve sexual function and prevent osteogenesis. However, precautions are necessary in therapies containing icariin due to its involvement in drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
(72 reference statements)
2
13
0
Order By: Relevance
“…[19]. We also showed Icariin, a natural prenylated flavonol glycoside popularly used to treat sexual dysfunction in males and osteoporosis remarkably impairs the substrate uptake via OATP1B1, OATP1B3 and OATP2B1, which observation is consistent with the early study [78,79].…”
Section: Organic Anion Transporting Peptides (Oatps)supporting
confidence: 87%
“…[19]. We also showed Icariin, a natural prenylated flavonol glycoside popularly used to treat sexual dysfunction in males and osteoporosis remarkably impairs the substrate uptake via OATP1B1, OATP1B3 and OATP2B1, which observation is consistent with the early study [78,79].…”
Section: Organic Anion Transporting Peptides (Oatps)supporting
confidence: 87%
“…Inhibition or stimulation of OATP2B1's function by drugs or foods could alter the pharmacokinetics of OATP2B1 substrates and potentially lead to adverse effects. Quite a few interactions between OATP2B1 and natural products have been reported in the literature (Fuchikami et al, 2006;Imanaga et al, 2011;Kock et al, 2013;Li et al, 2014;Mandery et al, 2010;Satoh et al, 2005;Shirasaka et al, 2013a,b;Tapaninen et al, 2010Tapaninen et al, , 2011Roth et al, 2011), suggesting that OATP2B1 could interact with a wide range of natural products. To identify more OATP2B1 modulators from natural products and to avoid potential adverse drug-drug and drug-food interactions, in this work the effects of 27 natural compounds and extracts on the function of OATP2B1 have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Roth et al (2011) reported that green tea catechins epicatechin gallate and epigallocatechin gallate significantly inhibited OATP2B1-mediated E3S uptake. Several flavonoids, silymarin flavonolignans, and antidiabetic drugs have also been reported to inhibit OATP2B1 in vitro (Bachmakov et al, 2008;Klatt et al, 2013;Kock et al, 2013;Li et al, 2014;Mandery et al, 2010). These reports demonstrated that OATP2B1 could interact with a wide range of natural products.…”
Section: Introductionmentioning
confidence: 92%
“…In vivo, scutellarin is highly distributed in hepatocytes, the same as the main target cells of HMG-GoA reductase statins 7 . Many Traditional Chinese Medicines (TCMs) active substances have significant effects on substrates of hepatic transporter and impact transport efficiency [8][9][10] . Transporters play a key role in drug pharmacokinetics and the competition for them is vital for drug uptake, distribution, and elimination 11,12 .…”
Section: Scutellarin Inhibition Of the Rosuvastatin Uptake In Rat Hepmentioning
confidence: 99%